Intratumoral pseudoaneurysm within a liver metastasis of gastric cancer: a case report - Hiroki Ohara; Yuji Ishibashi; Shuntaro Yoshimura; Ryoto Yamazaki; Fumihiko Hatao; Takeshi Koshiishi; Yasuhiro Morita; Kazuhiro Imamura (Surgical Case Reports, 2020)
Abstract Background Intrahepatic artery pseudoaneurysms are mostly iatrogenic and result from hepatobiliary interventions. The incidence of intrahepatic artery pseudoaneurysms within liver tumors without prior intervention is extremely rare. We presented herein the first report of a case of an intratumoral pseudoaneurysm within a liver metastasis of gastric cancer without any prior intervention during chemotherapy. Case presentation A 59-year-old male patient underwent a distal gastrectomy and D2 lymph node dissection for gastric cancer. He was treated in the emergency room for right abdominal pain following the 4th cycle of nivolumab administration as second-line chemotherapy after adjuvant chemotherapy with S-1 and first-line chemotherapy for a liver metastasis of gastric cancer with ramucirumab plus paclitaxel. CT showed a 72-mm metastatic liver tumor containing a 9-mm pseudoaneurysm and fluid collection around the hepatic edge. Intrahepatic artery pseudoaneurysm within the metastatic liver tumor was diagnosed, with the surrounding fluid indicating potential, active bleeding. An emergency angiography confirmed the presence of a pseudoaneurysm in the intrahepatic artery, which was embolized using microcoils. The contributory causes of the intratumoral pseudoaneurysm were assumed to be the following: (1) tumor necrosis leading to encasement, erosion of the vessel wall, and subsequent arterial wall weakening; and (2) inhibition of vascular endothelial growth by ramucirumab resulting in a vessel wall breach and pseudoaneurysm formation. Conclusion It is necessary to recognize that pseudoaneurysms can arise within a metastatic liver tumor during chemotherapy.